Pengaruh Halal Awareness dan Halal Certification terhadap Pilihan Konsumsi Halal Generasi Z pada Produk Korean Food: (Studi pada Konsumen Lawson Tulungagung) - Agus Eko Sujianto; Aprilia Nur Azizah; Muhammad Arif Budi Aji; Sa’adah Nurul Ummah; Tika Amelia Sulistyaningrum (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
Globalization is a global phenomenon that affects all aspects of life, including consumption behavior. The Korean Wave is an example of globalization. The Korean Wave phenomenon can reach Indonesia, one of which is through Korean music culture which is very famous in various countries, namely K-Pop. Apart from its well-known music, Korea also wants to export halal-certified Korean food to Indonesia through halal food diplomacy. This research aims to determine the influence of halal awareness and halal certification on generation Z's choice of halal consumption behavior for Korean food products. The population in this research is Lawson Tulungagung consumers. The sample used in this research was 160 respondents who had been tested to meet the sampling criteria. The analytical methods used are multiple linear regression, instrument testing, descriptive analysis, classical assumption testing, and hypothesis testing. The results of this research show that simultaneously halal certification and halal awareness have a positive and significant effect on generation z's halal consumption choices. Apart from that, halal certification partially has a negative and insignificant effect on generation z's halal consumption choices, while halal awareness has a positive and significant effect on generation z's halal consumption choices for Korean food products.